2015
DOI: 10.1038/sc.2015.53
|View full text |Cite
|
Sign up to set email alerts
|

Sexual satisfaction in women with spinal cord injuries

Abstract: Study design: Structured interview based on a predesigned survey. Objective: To examine the factors that affect the degree of sexual satisfaction in a sample of women with spinal cord injury (SCI). Setting: The study participants were women with SCIs, from the area of the SCI Unit of A Coruña, a reference unit for the Community of Galicia in the northwest of Spain. All study participants were selected consecutively in the outpatient clinic in 2013. Methods: The study included women with the American Spinal Inj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0
10

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 20 publications
2
13
0
10
Order By: Relevance
“…Access to a specialist HCP at all stages post-injury was also identified as valuable: Loss of continence and management of incontinence had a profound impact both on sexual self-image and ability to enjoy sexual activity. As in other papers [15,22], participants were anxious about their ability to be attractive to or to sexually please a partner and despite an increased emphasis on the emotional significance of sexuality many women reported an overall reduction in sexual satisfaction, particularly linked to loss of orgasm, in contrast to previous work [12]. Reflecting other studies [21] physical self-exploration was beneficial to some women and built their confidence, but for others was traumatic.…”
Section: "I Did Buy Myself a Dildo To See How I Would Feel To Experimentioning
confidence: 74%
See 1 more Smart Citation
“…Access to a specialist HCP at all stages post-injury was also identified as valuable: Loss of continence and management of incontinence had a profound impact both on sexual self-image and ability to enjoy sexual activity. As in other papers [15,22], participants were anxious about their ability to be attractive to or to sexually please a partner and despite an increased emphasis on the emotional significance of sexuality many women reported an overall reduction in sexual satisfaction, particularly linked to loss of orgasm, in contrast to previous work [12]. Reflecting other studies [21] physical self-exploration was beneficial to some women and built their confidence, but for others was traumatic.…”
Section: "I Did Buy Myself a Dildo To See How I Would Feel To Experimentioning
confidence: 74%
“…Psychosexual consequences may limit sexual activity and adjustment more than physical impairments [12,13] particularly regarding desire, subjective arousal, body image, self-esteem and self-confidence [12]. Relationships are also affected [12,13,14]; associations between stable relationships, sexual satisfaction and self-esteem have been identified [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…However, data saturation was reached far before the desired number of participants. (19) Not making use of patient leaflets (18) Insufficient weekend leave questionnaire (11) Ã (The number between brackets indicates how many times the facilitating condition or barrier has been mentioned by the respondents).…”
Section: Discussionmentioning
confidence: 99%
“…Major reasons for this discomfort are shame, inadequate knowledge, the belief that addressing the subject is improper and not being a topic of priority [11,13,18]. These restrictions may lead to the neglect of problems regarding patient sexuality as can be seen in several studies among persons with an SCI [19][20][21]. In these studies, persons with an SCI expressed dissatisfaction regarding the quality and quantity of sexualityrelated patient education during their rehabilitation [19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…Fritz et al [3] reported that in rehabilitation women are not receiving appropriate attention about the knowledge of sexuality. Healthy adjustment depends on sexual satisfaction and self-esteem [4]. Moreno-Lozano et al [5] said that walking is not always the most important function to recover in order to improve their quality of life but return to their sexual relation is needed to improve future quality of life.…”
Section: Introductionmentioning
confidence: 99%